2008
DOI: 10.21273/horttech.18.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Solids and Simple Sugars Measurement in Intact Mango Using Near Infrared Spectroscopy

Abstract: A rapid, reliable, and nondestructive method for quality evaluation of mango (Magnifera indica) fruit is important to the mango industry for international trade. The objective of this study was to determine the potential of near-infrared (NIR) spectroscopy to predict soluble solids content (SSC) and individual and combined concentrations of sucrose, glucose, and fructose nondestructively in mango. Mature mangoes at two different temperatures (15 °C and 20 °C) were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
(31 reference statements)
1
22
0
1
Order By: Relevance
“…The results reported by the authors indicated that NIR provides an efficient and alternative method and the results are comparable with other platforms the chemical reference methods (Brenna and Berardo, 2004;Cozzolino, 2015;Moncada et al, 2013). Delwiche et al (2008) developed the NIR equation and determined the potential of NIR to predict sucrose, glucose, and fructose content in mango with high precision. To confirm the reliability of NIR-generated phenotypic data, we performed QTL analysis using these data sets that are reported in the other sections of the manuscript.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The results reported by the authors indicated that NIR provides an efficient and alternative method and the results are comparable with other platforms the chemical reference methods (Brenna and Berardo, 2004;Cozzolino, 2015;Moncada et al, 2013). Delwiche et al (2008) developed the NIR equation and determined the potential of NIR to predict sucrose, glucose, and fructose content in mango with high precision. To confirm the reliability of NIR-generated phenotypic data, we performed QTL analysis using these data sets that are reported in the other sections of the manuscript.…”
Section: Resultsmentioning
confidence: 74%
“…Delwiche et al . () developed the NIR equation and determined the potential of NIR to predict sucrose, glucose, and fructose content in mango with high precision. To confirm the reliability of NIR‐generated phenotypic data, we performed QTL analysis using these data sets that are reported in the other sections of the manuscript.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of dissolved sugars (sucrose, glucose and fructose) in fruit juice is generally measured as TSS using a refractometer (Delwiche et al 2008). TSS values in the present study were considered as an index of sugar content.…”
Section: Resultsmentioning
confidence: 99%
“…Nondestructive methods have long been suggested as a means to evaluate fruit quality and near infrared spectroscopy (NIRS) is one of the analytical techniques that stand out (Abbott, ). Therefore, many studies can be found with bench top and/or on‐line NIR spectrometers estimating soluble solids content (SSC), dry matter content (DM), titratable acidity (TA), firmness, starch content, and other quality parameters in mango fruit (Delwiche, Mekwatanakarn, & Wang, ; Mahayothee, Leitenberger, Neidhart, Mühlbauer, & Carle, ; Nicolaï et al, ; Saranwong, Sornsrivichai, & Kawano, ; Schmilovitch, Mizrach, Hoffman, Egozi, & Fuchs, ; Valente, Leardi, Self, Luciano, & Pain, ).…”
Section: Introductionmentioning
confidence: 99%